Asparagine: an amide of particular distinction in the regulation of symbiotic nitrogen fixation of legumes. (September 2013) - Sulieman, Saad; Tran, Lam-Son Phan
Abstract : Symbiotic nitrogen fixation is tightly regulated by a range of fine processes at the nodule level, over which the host plant has overall control through the whole life of the plant. The operation of this control at the nodule level is not yet fully understood, but greater knowledge will ultimately lead to a better improvement of N2 fixation through the use of crop legumes and genetic engineering of crop plants for higher performance. It has been suggested that, nodule responses to the nutritional complexity of the rhizosphere environment involve a great deal of coordination of sensing and signal transduction. This regulation can be achieved through several mechanisms, including changes in carbon metabolism, oxygen supply and/or overproduction of reactive oxygen and nitrogen species. Recently, the cycling of amino acids observed between the plant and bacteroid fractions suggests a new and important regulatory mechanism involved in nodule responses. Most of the recent transcriptional findings are consistent with the earlier biochemical and physiological reports. Current research revealed unique advances for nodule metabolism, especially on the regulation of asparagine synthetase gene expression and the control of asparagine (ASN) to N2 fixing activity. A large amount of ASN is found accumulating in the root nodules of the symbiotic plants under restricted environments, such as drought, salinity and nutrient deficiency. Exceptionally, ASN phloem feeding has resulted in an increased concentration of the ASN amide in nodules followed by a remarkable decrease in nodule activity. In this review, recent progress concerning the possible role of ASN in whole-plant-based down-regulation of symbiotic N2 fixation will be reviewed.